Policy of Teon Nila Serua Community Settlement Program in Waipia Central Maluku - Simona CH Litaay; Andi Agustang; Muhammad Syukur (Universitas Padjadjaran, 2023)
This study purposes in determining social phenomena regarding the policies of the Teon Nila Serua (TNS) community settlement program in Waipia, Central Maluku. It started from the adaptation process, asset ownership, and knowledge of modern agriculture, challenges, and obstacles in the archipelago. The method conducted in this study is a qualitative method with a phenomenological type. The results show that the resettlement program for the TNS community in Waipia did not produce social welfare because the community had difficulty adapting to their new habitus, there was a mismatch of work culture, a top-down elitist approach, the erosion of social solidarity that lives and belongs to the island community and several other traditions that are increasingly disappearing, are also influenced by the modernization process marked by advances in information and communication technology, as well as a lack of mature planning from the government, resulting in a gap between plans and implementation that is less effective and efficient.